2015
DOI: 10.3389/fpsyg.2015.00769
|View full text |Cite
|
Sign up to set email alerts
|

The student-institution fit at university: interactive effects of academic competition and social class on achievement goals

Abstract: As compared to continuing-generation students, first-generation students are struggling more at university. In the present article, we question the unconditional nature of such a phenomenon and argue that it depends on structural competition. Indeed, most academic departments use harsh selection procedure all throughout the curriculum, fostering between-student competition. In these departments, first-generation students tend to suffer from a lack of student-institution fit, that is, inconsistencies with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 93 publications
2
18
0
2
Order By: Relevance
“…Interestingly, in an early hierarchical model of achievement motivation, Elliot () already indicated that: ‘Research on various forms of avoidance motivation (…) suggests that women, ethnic minorities, and individuals from lower socioeconomic backgrounds and interdependent cultures may be most susceptible to performance‐avoidance regulation’ (p. 175). However, this idea has only received moderate support (e.g., see Berger & Archer, ; Sommet, Quiamzade, Jury, & Mugny, ). We believe the present findings importantly clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in an early hierarchical model of achievement motivation, Elliot () already indicated that: ‘Research on various forms of avoidance motivation (…) suggests that women, ethnic minorities, and individuals from lower socioeconomic backgrounds and interdependent cultures may be most susceptible to performance‐avoidance regulation’ (p. 175). However, this idea has only received moderate support (e.g., see Berger & Archer, ; Sommet, Quiamzade, Jury, & Mugny, ). We believe the present findings importantly clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, first‐generation college students are more likely to be afraid of failure (Bui, ) and thus more likely to endorse performance‐avoidance goals in college (i.e., trying not to be outperformed by others, Jury, Smeding, Court, & Darnon, ; Jury, Smeding, & Darnon, ) than continuing‐generation students. Moreover, in competitive departments (e.g., civil engineering), first‐generation college students are more likely to experience less fit and consequently, more difficulty in maintaining mastery‐goal endorsement (i.e., desire to progress, to master tasks), compared with continuing‐generation students (Sommet, Quiamzade, Jury, & Mugny, ). Such motivation regulation may be particularly problematic for these students, due, notably, to the negative links usually observed between performance‐avoidance goal endorsement and academic performance (Van Yperen, Blaga, & Postmes, ).…”
Section: The Psychological Barriers Faced By Low‐ses Students In Highmentioning
confidence: 99%
“…Moreover, although sampling was performed from a university library from among a variety of different physicians, this library was not representative of all libraries in the country. Lastly, the lack of assessment of previous educational level, predisposing factors to educational failure, social background 70 and specialty preferences are further limitations.…”
Section: Discussionmentioning
confidence: 99%